Does the processing of hypnotic analgesia require attention-demanding resources? : a dual task analysis of hypnotic-susceptibility-mediated differences in executive attentional processing between hypnotic and nonhypnotic analgesia : a thesis presented in part fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Smeets, Louis (Massey University, 2000)
There is substantial evidence that hypnotic analgesia can be effective in reducing pain and distress in both experimental and clinical settings in at least a sizeable portion of the population. However, the mechanism whereby hypnosis achieves this are not well-understood and various explanations have been proposed. These offer fundamentally different predictions about the attentional involvement of hypnotic analgesia, which are highly relevant to pain research as the disruption of ongoing activity is one of the more debilitating aspects of pain. While cognitive-behavioural coping strategies may attenuate pain of short duration, their effortful deployment further interferes with ongoing activity, and there are strong indications that their effectiveness rather rapidly decreases as pain perseveres. If as dissociated-control theory proposes, hypnotic analgesia does not require attentional effort for its execution, it would provide significant advantages for individuals who can effectively achieve it (i.e., those who are highly susceptible to hypnotic suggestions). This hypothesis was further tested in an experimental study using a dual-task scenario and repeated-measures design. One hundred and ninety student volunteers were first screened for hypnotic susceptibility using the Hardvard Group Scale of Hypnotic Susceptibility: Form A, and seventy-eight also completed a more demanding follow-up assessment using the Waterloo-Stanford Group C scale. This resulted in fifty individuals who qualified for participation in the experimental part of the study by scoring as either high or low hypnotisable on both these measures. Of these, 12 lows and 14 highs went on to take part in an experimental study that had high and low hypnotisables performed a cognitively demanding tracking task while using either hypnotic analgesia or cognitive-behavioural strategies to cope with iontophoretically administered pain. Interruption of tracking performance during each coping method was used as a measure of central attentional resources needed to execute that coping strategy. Results did not find evidence for the hypothesised absence of interference effects among high hypnotisables using hypnotic analgesia. Possible reasons are examined and exploration of data indicates that the tracking task was not difficult enough to require significant and continuous attention, and lacked sensitivity to distinguish interference effects between treatment conditions. Findings do not allow a conclusion of support for either explanation of the mechanisms underlying effective hypnotic analgesia. Highly hypnotisable subjects using hypnotic analgesia did achieve significantly greater reductions in both the intensity and unpleasantness of the pain than low hypnotisables using hypnotic analgesia or high and low hypnotisables using cognitive-behavioural coping strategies. Characteristics of the attentional capture of visual motion are discussed and suggestions made for future research and improvements to the design of the current study. Considerable attention is given to findings of a large body of neurophysiological studies of brain activity and a proposed neuropsychophysiological model of hypnosis. When combined, results of these studies indicate that: the mechanisms of attentional control involved in the process of hypnosis are fundamentally different from those involved in the use of standard cognitive-behavioural strategies, but that both processes do require central attentional effort and resources.
Keywords: Hypnotism -- Therapeutic use; Analgesia -- Psychological aspects; Pain -- Treatment; Attention; Neuropsychology